Redemption Discounts Before Due on Financing Home Ownership Loans at Bank Syari'ah Indonesia - Shafra, Shafra; Jayusman, Jayusman; Inastia, Amira (ASAS, 2023)
This research describes the cut repayment of mortgage financing before maturity at Bank Syari'ah Indonesia KCP Kedaton Bandar Lampung. In giving these discounts, BSI was not the same from one customer to another. The focus of this research was: How is the analysis of DSN MUI fatwa No.23/DSN-MUI/III/2002 on the application of Deductions in Murabaha contracts at BSI KCP Bandar Lampung? The purpose of this study is to analyze the DSN MUI fatwa No.23/DSN-MUI/III/2002 on the application of deductions in murabahah contracts at BSI KCP Bandar Lampung, This type of research is a type of field research (field research), which Research to Bank Syari'ah Indonesia KCP Kedaton Bandar Lampung customers.   Research this is characteristic descriptive-analytic in nature, namely research that aims to describe, describe and interpret in more detail related to the problem under study by studying it in depth. The conclusion from this study was that for customers who apply for redemption before maturity in Murabahah KPR financing at BSI KCP Kedaton, namely that there were differences in the application of pre-payment deductions. The existence of this difference is based on the customer's achievements in a Murabahah transaction, making payment on time or faster than the agreed time and giving the discount provided that it was not agreed upon in the contract. The size of the discount was left to the bank's policies and considerations. This was in line with the DSN MUI fatwa No. 23/DSN-MUI/III/2002.Keywords: Murabahah, KPR Financing, Discounts